Differences in Obstetrical Care and Outcomes Associated With the Proportion of the Obstetrician's Shift Completed. Issue 3 (24th September 2022) - Yee, L.M.; McGee, P.; Bailit, J.L.; Wapner, R.J.; Varner, M.W.; Thorp, J.M.; Caritis, S.N.; Prasad, M.; Tita, A.T.N.; Saade, S.R.; Sorokin, Y.; Rouse, D.J.; et al.
Abstract : ( Am J Obstet Gynecol . 2021;225:430.e1–11) Obstetric provider decision-making may influence the quality of care. Previous studies have examined differences in provider decisions and obstetric outcomes based on time of day, though this may not accurately capture provider fatigue. This study examined provider decisions and obstetric outcomes in the context of the proportion of time completed by the provider in their work shift at the time of delivery.